2009
DOI: 10.1002/cncr.24375
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity translates into excellent local control in extremity myxoid liposarcoma

Abstract: Multidisciplinary management of extremity STS achieves high rates of local control. Myxoid liposarcoma is associated with higher rates of local control compared with other STS subtypes, after combined surgery and radiation, suggesting a particular radiosensitivity that can be exploited to improve oncologic outcome in appropriate cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
116
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 35 publications
13
116
1
2
Order By: Relevance
“…Estimated 5-year local recurrence-free survival remained high (88.2%), similar to our historical rate of 89.6% in extremity STS treated with surgery and external beam RT. 26 Because all patients have been followed for at least 2 years, this rate is unlikely to change substantially. The Memorial Sloan-Kettering Cancer Center group also found no increase in local relapse risk with IMRT, with a 5-year estimated local control rate of 94%, 10 decreasing to 92% when updated with additional patients in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated 5-year local recurrence-free survival remained high (88.2%), similar to our historical rate of 89.6% in extremity STS treated with surgery and external beam RT. 26 Because all patients have been followed for at least 2 years, this rate is unlikely to change substantially. The Memorial Sloan-Kettering Cancer Center group also found no increase in local relapse risk with IMRT, with a 5-year estimated local control rate of 94%, 10 decreasing to 92% when updated with additional patients in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, delicate plexiform vasculature with perivascular sclerosis, hyalinizing rosettes, strong cytoplasmic staining with MUC4 are present [12]. Finally, low grade myxofibrosarcoma, on the other hand, is characterized by fusiform tumor cells, with indistinct cell borders, slightly eosinophilic or vacuolated cytoplasm, and varying degree of hyperchromatic atypical nuclei, set in a myxoid or fibromyxoid matrix containing elongated, curvilinear capillaries with perivascular cell condensation [13][14][15][16][17][18]. However, the absence of lipoblasts and diffuse positive staining for S100 aid the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Different studies have suggested that MLS tends to be relatively more radiosensitive than other types of STS, with high rates of regression and even complete clinical response. 7 The National Comprehensive Cancer Network (NCCN) panel guidelines for stage II-III MLS are: For resectable tumors, surgery followed by radiotherapy is the primary treatment. If the tumor is unresectable, neoadjuvant therapies (radiotherapy, chemoradiation, chemotherapy) are recommended primarily, even if some authors have not found any improvement in overall survival.…”
Section: Discussionmentioning
confidence: 99%